The Effects of the Pandemic on Romanian Incoming Tourism - Mihnea Toncescu (Romanian Economic Journal, 2024)
In this paper we study the impact of Covid-19 pandemics on the incoming tourism in Romania. Following the typology of crises in general and the specific nature of the Covid crisis, we will see what effects this most recent pandemic had globally and what economic policies were taken to counteract the adverse effects of the pandemic. We will see that the lockdown and mobility restrictions at European level have led to a free fall of the incoming tourism, increasing the share of domestic tourism on the one side, while on the other hand we observe the tendency of people to move to the countryside. There have been observed some trends that favoured nature tourism, but we also witnessed, that OECD recommends continuing with a more sustainable tourism. We witnessed in 2022 a recovery of tourism in the European Union, which seems to invalidate the trends reiterated by OECD. Through a statistical regression we try to forecast the trend of incoming tourism in Romania, which gives us two possible directions of its evolution. Analysing the pessimistic case, we also identify systemic risks at the level of Romanian incoming tourism, that is focusing on a few countries only, so we see diversification as a very urgent matter for Romanian tourism.